"Once I enter the class, I just feel like in the middle of nowhere": a narration of ESP teacher's emotional geographies - Isnawati, Uzlifatul Masruroh; Rahayu, Nanik Sri (Journal on English as a Foreign Language, 2023)
While studies on the teaching of English for specific purposes (ESP) in higher institutions have been widely explored, there is a paucity of research addressing how ESP teachers in higher education deal with their emotional geography when teaching ESP. The data of this present study were garnered through in-depth interviews and analyzed following Braun and Clarke